Cover Image, Volume 16, Issue 3. Issue 3 (5th September 2022) - Unknown
Abstract : On the cover : 'Cameo' club wheat has resistance to multiple biotic and abiotic stressors and is best adapted to northeastern Oregon, northern Idaho, and eastern Washington. See K. Garland‐Campbell et al., "Registration of 'Cameo" soft white winter club wheat, " https://doi.org/10.1002/plr2.20204 . Photo by Kimberly Garland‐Campbell.